Early Literacy and Numeracy in Early Childhood: A Systematic Literature Review of Research Trends and Practices - Theresia Alfiani Sum; Christina Ismaniati; Jumadi Jumadi (Lembaga Bale Literasi, 2025)
Literacy and numeracy are fundamental skills that play a crucial role in supporting learning processes and cognitive development across educational levels. However, research on literacy and numeracy remains fragmented across multiple disciplines, necessitating a systematic synthesis to obtain a comprehensive overview of the development of this field. This study aims to analyze and synthesize findings from previous research on literacy and numeracy using a Systematic Literature Review (SLR) approach to identify research trends, effective interventions, methodological characteristics, and existing research gaps. The method employed was a systematic literature review following structured stages, including problem formulation, literature search, article screening, quality appraisal, and data synthesis. The findings indicate that SLR plays a significant role in integrating diverse research outcomes, identifying effective instructional strategies, and providing an evidence base for the development of educational policies and practices. In addition, this review reveals methodological limitations in several previous studies and identifies factors influencing the development of literacy and numeracy, such as learning environments, instructional approaches, and the use of technology. These findings underscore the importance of an interdisciplinary perspective in advancing future research on literacy and numeracy. Overall, the implementation of SLR provides a comprehensive evidence base to support evidence-based decision making, enhance the quality of educational practices, and guide future research in a more systematic and focused manner.